Gas mixture composition control in fine organic synthesis - М.Е. Гусельников; Ю.В. Анищенко; А.С. Гынгазов; А.К. Аймуханов (Қарағанды университетінің хабаршысы. Физика сериясы)
Fine organic synthesis includes a large number of stages. All its stages require determining the small quantities of impurities for initial and intermediate synthesis products. Fine organic synthesis is a complex process requiring automation. To automate the synthesis products’ control device it is necessary to use the modern physico-chemical methods, which perform continuous measurements with high speed. This paper describes the hardware implementation of a device, based on infrared absorption analysis method. The absorption methods of substance composition analysis are based on the absorption of sounding radiation by the analysed component. The strength of the probing radiation passing through the mixture changes slightly at the small concentrations of the analysed component. Therefore, there is a problem of measuring small changes of a large signal. The absorption method of substance composition analysis can be used for analysis the composition of mixtures of gaseous organic substances. It enables to scan the optical frequency of the probe radiation by changing the angle of the interference filter. The proposed equipment allows determining the concentration of substances by overlapping their absorption spectra of infrared radiation.